2017
DOI: 10.1364/prj.6.000047
|View full text |Cite
|
Sign up to set email alerts
|

On-chip polarization splitter based on a multimode plasmonic waveguide

Abstract: The miniaturization of polarization beam splitters (PBSs) is vital for ultradense chip-scale photonic integrated circuits. However, the small PBSs based on complex hybrid plasmonic structures exhibit large fabrication difficulties or high insertion losses. Here, by designing a bending multimode plasmonic waveguide, an ultrabroadband on-chip plasmonic PBS with low insertion losses is numerically and experimentally realized. The multimode plasmonic waveguide, consisting of a metal strip with a V-shaped groove on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, we note here that the polarization-controlled SPPs excitation examined thus far depend either on x-polarized and y-polarized incidences or on LCP and RCP incidences, only two polarization states of incident light can be splitted in one structure [20][21][22]. In order to address this problem, Shen et al demonstrated a bi/tridirectional SPPs splitter based on a slanted gold mushroom array [23], achieving different responses to multiple incident light polarization states.…”
Section: Introductionmentioning
confidence: 95%
“…However, we note here that the polarization-controlled SPPs excitation examined thus far depend either on x-polarized and y-polarized incidences or on LCP and RCP incidences, only two polarization states of incident light can be splitted in one structure [20][21][22]. In order to address this problem, Shen et al demonstrated a bi/tridirectional SPPs splitter based on a slanted gold mushroom array [23], achieving different responses to multiple incident light polarization states.…”
Section: Introductionmentioning
confidence: 95%
“…[ 3,4 ] As an essential component of on‐chip integrated photonic devices, polarization router can separate and steer light with different polarizations of transverse electric (TE) and transverse magnetic (TM) modes into different output ports, so as to realize polarization division multiplex of channels. In the past few years, polarization routers are generally realized based on gratings, [ 5–8 ] optical waveguides, [ 9–12 ] photonic crystals, [ 13–16 ] plasmonic structures, [ 17–20 ] metamaterials [ 21–23 ] or some other structures. [ 24–27 ] Polarization routers based on gratings or waveguides usually possess simple configurations and high extinction ratio, but the large size restricts the practical applications for on‐chip dense integration.…”
Section: Figurementioning
confidence: 99%
“…[ 13,16 ] The plasmonic polarization routers are broadband and have smaller size, but usually possess large loss. [ 17,18 ] Polarization routers based on metamaterials have high efficiency, but the fabrication process is complicated and the size is relatively large. [ 21,23 ] Large size and low‐efficiency excitation of traditional design cause the polarization routers to be difficult to meet the requirements of high‐density on‐chip integration.…”
Section: Figurementioning
confidence: 99%